2016
DOI: 10.1038/srep38966
|View full text |Cite
|
Sign up to set email alerts
|

The concept of entropic rectifier facing experiments

Abstract: The transport of molecules in confined media is subject to entropic barriers. So theoretically, asymmetry of the confinement length may lead to molecular ratchets with entropy as the only driving force for the biased transport. We address experimentally this question by performing alternative ionic current measurements on electrolytes confined in neutral conical nanopores. In case anions and cations widely differ in size, we show that rectification of ionic current can be obtained that depends on ions size and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Recently it has been shown that novel dynamical regimes appear when the section of the confining vessel is not constant. Indeed, asymmetric pores have been used to pump [22] and to rectify ionic currents [23][24][25][26][27]. Moreover, recirculation has been reported for electrolytes confined between corrugated walls [28][29][30][31], and the variation in the section of the channels can tune their permeability [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been shown that novel dynamical regimes appear when the section of the confining vessel is not constant. Indeed, asymmetric pores have been used to pump [22] and to rectify ionic currents [23][24][25][26][27]. Moreover, recirculation has been reported for electrolytes confined between corrugated walls [28][29][30][31], and the variation in the section of the channels can tune their permeability [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…With Eqs (26). and(27) it is easy to show that ∆γ = µ + (x, y) + µ − (x, y) and ∆ξ = µ + (x, y) − µ − (x, y), i.e., that ∆γ and ∆ξ are the sum and difference of the full chemical potentials at order O(f ).…”
mentioning
confidence: 99%
“…Understanding transport of ions, molecules, cells and colloids in nano-and micro-fluidic devices is of primary relevance for its biological and technological applications. For example, the transport across synthetic [1][2][3] and biological [4,5] channels and pores is controlled by their shape, as well as by the effective interactions between channel walls and the transported objects. Similarly, in micro-and nano-fluidic circuitry the shape of the channel has been exploited to realize fluidic transistors [6] or diodes [7][8][9] and to control ionic [10,11] and electro-osmotic [12] fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…We scale the lengths with the unit length 2L, times with the diffusion time In our case the validity of the Fick-Jacobs approach requires that the dimensionless frequency ω has to be smaller than one, this implies modulations smaller than 10 Hz approximately. This range is of the order of the ones used in recent experiments on transport of molecules in confined media subject to entropic barriers and to a driving force 29 .…”
Section: The Modelmentioning
confidence: 95%